'It'd be useful, but I wouldn't use it': barriers to university students' feedback seeking and recipience. Issue 11 (2nd November 2017) - Winstone, Naomi E.; Nash, Robert A.; Rowntree, James; Parker, Michael
Abstract : For feedback to be effective, it must be used by the receiver. Prior research has outlined numerous reasons why students' use of feedback is sometimes limited, but there has been little systematic exploration of these barriers. In 11 activity-oriented focus groups, 31 undergraduate Psychology students discussed how they use assessment feedback. The data revealed many barriers that inhibit use of feedback, ranging from students' difficulties with decoding terminology, to their unwillingness to expend effort. Thematic analysis identified four underlying psychological processes: awareness, cognisance, agency, and volition. We argue that these processes should be considered when designing interventions to encourage students' engagement with feedback. Whereas the barriers identified could all in principle be removed, we propose that doing so would typically require – or would at least benefit from – a sharing of responsibility between teacher and student. The data highlight the importance of training students to be proactive receivers of feedback.